2023
DOI: 10.7717/peerj.15191
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-specific knockout of HIF-2α cannot alleviate carbon tetrachloride-induced liver fibrosis in mice

Abstract: Background The effects of hypoxia inducible factor-2α (HIF-2α) deficiency on liver fibrosis have not been demonstrated in a fibrosis model induced by carbon tetrachloride (CCl4). We aimed to examine whether hepatocyte-specific HIF-2α deletion could ameliorate CCl4-induced liver fibrosis in mice. Methods Hepatocyte-specific HIF-2α knockout mice were created using an albumin promoter-driven Cre recombinase. HIF-2α knockout (KO) mice and floxed control wild-type (WT) mice were fed a normal diet (ND) and receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Hyp is an amino acid unique to collagen, and many diseases can be accompanied by changes in collagen metabolism, causing altered blood, urine, and tissue Hyp levels. Hyp levels in the liver are an important index reflecting the degree of liver fibrosis, and increased Hyp levels in the liver imply increased liver fibrosis ( Bedair et al, 2023 ; Ye et al, 2023 ). Here, we determined Hyp levels in the liver tissue of the rats and found that the Hyp level was the highest in the NAFLD + CIA group, followed by NAFLD group.…”
Section: Resultsmentioning
confidence: 99%
“…Hyp is an amino acid unique to collagen, and many diseases can be accompanied by changes in collagen metabolism, causing altered blood, urine, and tissue Hyp levels. Hyp levels in the liver are an important index reflecting the degree of liver fibrosis, and increased Hyp levels in the liver imply increased liver fibrosis ( Bedair et al, 2023 ; Ye et al, 2023 ). Here, we determined Hyp levels in the liver tissue of the rats and found that the Hyp level was the highest in the NAFLD + CIA group, followed by NAFLD group.…”
Section: Resultsmentioning
confidence: 99%